2016
DOI: 10.3390/s16010112
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Aware Routing Map for Indoor Evacuation

Abstract: Knowledge of dynamic environments expires over time. Thus, using static maps of the environment for decision making is problematic, especially in emergency situations, such as evacuations. This paper suggests a fading memory model for mapping dynamic environments: a mechanism to put less trust on older knowledge in decision making. The model has been assessed by simulating indoor evacuations, adopting and comparing various strategies in decision making. Results suggest that fading memory generally improves thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Simulations adopt a five level departmental building, which has already been used for testing (purely) decentralized evacuation [2]. This building consists of three rectangular blocks.…”
Section: The Buildingmentioning
confidence: 99%
See 4 more Smart Citations
“…Simulations adopt a five level departmental building, which has already been used for testing (purely) decentralized evacuation [2]. This building consists of three rectangular blocks.…”
Section: The Buildingmentioning
confidence: 99%
“…All the knowledge is time stamped and may have become out of date due to the evolution of the disaster, thus introducing uncertainty to the knowledge. Zhao and Winter [2] addressed the uncertainty of knowledge by developing a fading memory model which trusted less the older knowledge. They found that the fading memory model generally improved the evacuation process.…”
Section: Evacuation Optimizationmentioning
confidence: 99%
See 3 more Smart Citations